المجتمع المدني التونسي و ازدواجية الدور السياسي و الاجتماعي - خليف, كربوع (جامعة الوادي.University eloued, 2021)
عتبر المجتمع المدني فاعلا رئيسيا في الحقل السياسي في تونس عبر تاريخه، ولقد زادت ثورة 2011 والدور الرائد للمجتمع المدني في عملية الانتقال الديمقراطي، من الاحتفاء به محليا ودوليا من خلال تعيين وزير في الحكومة مكلف بالصلة بالمؤسسات الدستورية والمجتمع المدني ومنح جائزة نوبل للسلام للحوار الوطني التونسي الذي اداره المجتمع المدني باقتدار سنة 2015. ولكن رغم تلك المكانة يجب الاقرار ان المجتمع المدني التونسي ظل عاجزا عن تلبية المطالب الاجتماعية والاقتصادية خصوصا للمناطق الداخلية والمعطلين عن العمل. تتناول هذه الدراسة طبيعة العلاقة بين المجتمع المدني والدولة في تونس، ومختلف السياقات والعوامل التي ادت الى تعاظم ادواره السياسية في مقابل الادوار الاجتماعية، ومدى تأثير ذلك على وظيفية منظمات المجتمع المدني في تونس. Civil society has been a major player in Tunisia's political field throughout its history, and the 2011 revolution and the leading role of civil society in the democratic transition have increased its celebration locally and internationally by appointing a minister in charge of constitutional institutions and civil society and awarding the Nobel Peace Prize for tunisian national dialogue, which was ably administered by civil society in 2015. But despite this status, it must be acknowledged that Tunisian civil society has been unable to meet social and economic demands, especially for the internal and unemployed regions. This study examines the nature of the relationship between civil society and the state in Tunisia, the different contexts and factors that led to the increase in its political roles as opposed to social roles, and the extent to which this affects the functioning of civil society organizations in Tunisia.
مجلد 12 العدد 02
Keywords: المجتمع المدني؛ تونس؛ الادوار السياسية؛ الادوار الاجتماعية؛; ivil society; Tunisia; Political roles; Social roles